(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
Food production and concern on the environment in the technological process and development have an important role to minimize the impact caused by the production of effluents from pig breeding, comparatively to human sanitary effluents. The installations of a pig farm were investigated and physical-chemical and micro-biological analyses of the effluent were undertaken. Thermo-tolerant coliform counts were performed after 24 hours of incubation. Counting detected coliforms at a rate of 241960 NMP/100 mL. Diluted samples 1:10 were employed to determine total nitrogen rates, due to the small detection band of the apparatus. Entry nitrogen was 11.5 mg/L while it amounted to 4.2 mg/L at exit. According to assays undertaken, the treatment of the effluent on the farm complies with Resolution by Conama 357/2005 with an effective decrease in coliforms, BOD, and N and P concentrations.